Characteristics of Javan Coucal (Centropus nigrorufus) Preferential Habitat in Wonorejo Surabaya - Suwarti, Muji; Mulyani, Yeni A.; Kartono, Agus P. (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
Javan coucal (Centropus nigrorufus) is one of the endemic birds of Java that has limited distribution in coastal areas. This study aimed to determine the spatial distribution and habitat preference of javan coucal in Wonorejo Region, in the East Coast of Surabaya. The spatial distribution and habitat preference were analyzed using dispersion index (ID) and Jacob index respectively. The results showed that Javan Coucal distribution was clumped, indicated by ID value > 1 for mangrove forests, inactive ponds and active ponds. The Jacob index (Dhi) were 0,75, 0,41 and -0,68 for inactive ponds, mangrove forests and active ponds, respectively. This result indicated that javan coucal preferred inactive ponds and the mangrove forests, and they tend to avoide active pond. The habitat factors affecting the javan coucal encounters were perch height (t=2,655; p=0,014), distance from coast (t=4,539; p=0,000) and air temperature (t=2,675; p=0,013). The regression equation was Y=67,041+0,678 (perch height) + 0,020 (distance from coast)-2,373(air temperature). Keywords: habitat preference, javan coucal, spatial distribution, Wonorejo